Encapsulation of Thiotepa and Altretamine as neurotoxic anticancer drugs in Cucurbit[n]uril (n=7, 8) nanocapsules: A DFT study - Hassanzadeh, Keyumars; Akhtari, Keivan; Esmaeili, Sara Sheikh; Vaziri, Azin; Zamani, Hedyeh; Maghsoodi, Mobina; Noori, Shamim; Moradi, Atefeh; Hamidi, Pardis (Journal of theoretical & computational chemistry, 2016)
The encapsulation of Altretamine (ALT) and Thiotepa (THI) as neurotoxic anticancer drugs in Cucurbit[ n ]uril (CB[ n ]) family of macrocycles ( n = 7 ,8) have been investigated and their potential in drug delivery, ability to provide physical and chemical stability, improving water solubility and decreasing the side effects have been studied using density functional theory (DFT) approach with B3LYP and the dispersion corrected functional WB97XD methods by employing the 3-21G* basis set. All the calculations were evaluated for gas phase and water as a pharmaceutical and biological solvent according to the polarizable continuum model (PCM). The non-covalent inter-molecular interactions between the host and guest parts were visualized using reduced density gradient analysis. The molecular characteristics for drugs, CB[ n ] and their complexes calculated and the global and local descriptors were employed to study the chemical stability of the host–guest complexes. The results show that the encapsulation of THI and ALT for both CB[7] and CB[8] energetically favorable and this can decrease the central nervous system (CNS) neurotoxicity, and increase the stability of THI in electrophilic and nucleophilic. Beside the CNS neurotoxicity reduction and increasing the stability in electrophilic and nucleophilic attacks, the solubility in water for ALT was improved. Thiotepa and Altretamine are widely used anticancer drugs with some undesirable side effects. Encapsulation of Thiotepa and Altretamine in Cucurbit[n]uril was investigated using the density functional theory. The adsorption energies and NCI-RDG study show the ease formation of the host-guest complexes. Global and local descriptors show reduction of side effects for the capsulated drugs.